Síntomas afectivos en estudiantes universitarios de enfermería durante la pandemia COVID-19 (2024)
This work approaches the COVID-19 pandemic, which represented a public health emergency due to the high risk of transmission; however, beyond the consequences on the state of physical health, it is necessary to recognize the repercussions in the mental health of the population, especially in university nursing students, because due to various situations associated with this pandemic and its confinement, they presented various affective symptoms, generating difficulties in different daily aspects. Objective: to describe the aspects known in the scientific literature about the affective symptoms that began during the COVID-19 pandemic in nursing students